PELAKSANAAN PERJANJIAN LISENSI ANTARA PEMBERI LISENSI DENGAN PENERIMA LISENSI PADA RAHASIA DAGANG - Herlina Ratna (KEADILAN PROGRESIF, 2020)
Trade secrets are information that is not generally known in the field of technology or business, including a formula, patterns, compilation, programs, methods, techniques or processes that produce economic value because it is useful in business activities. Problems in writing this thesis are: How is the implementation of the licensing agreement between the licensor and the licensee on trade secrets, this study uses a normative and empirical juridical approach method with a focus on secondary data supported by primary data. Data sourced from secondary data and primary data, then the data collected was analyzed in a qualitative juridical manner. Based on the research results of the implementation of the licensing agreement between the licensor and the licensee on trade secrets must meet the requirements including the granting of a permit by the holder of trade secret rights, which is set forth in the form of an agreement where the granting of rights is only to enjoy economic benefits that are not transferring trade secret rights. who are given protection. Suggestions should the parties can fulfill the rights and obligations stipulated in the form of a trade secret licensing agreement, so that it will bring economic benefits to both parties,